Some aspects of training future teachers to innovate - Репко, І. П. (Scientific notes of the pedagogical department, 2017)
Innovative activity is associated primarily with the willingness of teachers to the development and implementation of pedagogical innovations in educational process. However, the lack of willingness of teachers to adopt and put into practice greatly reduces their effectiveness. As a student in future teachers it is necessary to generate a innovative style of mental activity: to plan the sequence of actions; formulate test hypothesis; develop a program of observation, study best practices and carrying out pedagogical experiment; to process, organize and compile the data, draw conclusions and predict activities in the future. The modern UNIVERSITY needs innovative education, which based on new knowledge and innovation dynamics, and the characteristic properties are anthropocentrism, self-management, professionalism. Aims of innovative education in the University is to provide a high level of intellectual and spiritual personal development of the student; the creation of conditions for mastering the skills of scientific style of thinking; development of methodology innovations in the professional field. The author is a supporter of the activity approach to the formation of readiness of future teachers to innovative activity, that is professional qualities of future teachers are formed and manifested in the activity, through the solution of various problems arising in the process of professional-pedagogical training at the UNIVERSITY. The article reveals the peculiarities of innovative education and reveals the possibilities of the educational process of the modern UNIVERSITY for the formation of readiness for innovative activity of future teacher of educational institution. The author describes the main stages, the role of theoretical knowledge, practical training and teaching practice in the organization of an integrated system of training for innovation of future teachers. The article indicated that the preparation of students of pedagogical universities to innovation in teaching activities should be carried out through the formation of readiness to perception, learning scientific research, innovative practices of other teachers, its introduction into a new environment, developing their own innovations, the organization and conduct experiments, compile their own innovative teaching practices.